Cultivo de coriandro en invernadero para su consumo en fresco en San Pedro, Buenos Aires, Argentina - Paunero, Ignacio Eugenio (2021)
Coriander is consumed fresh as part of dishes in countries of America, Southeast Asia and India. In Argentina, the yield of its grains has been studied, although no publications have been found of fresh coriander yield and quality. The objective of this study was to determine the yield and quality of greenhouse-grown coriander for fresh consumption. At the San Pedro Agricultural Experiment Station, fresh matter yields and number of cuts before flower scape elongation were evaluated during three seasons in the cultivars Wenceslao INTA and Quique INTA, both created at that station. Four rows of plants spaced 20 cm apart were planted on ridges with drip irrigation. Two 50 cm samples were cut from the central rows where maximum height, apical leaf width, number of plants, fresh weight per square meter and quality were measured. Pests and diseases were observed. Fertilization was not carried out. Analysis of variance and Tukey's test (α = 0.05) were performed. In both cultivars, three cuts of fresh coriander of excellent quality were made with a total yield between 2.14 and 2.68 kg*m2 for Wenceslao INTA, and 1.86 to 2.96 kg*m2 for Quique INTA. No clear difference in yields was observed. There were no limiting pests for the crop.